ANALYSIS OF RHODAMIN-B CONTENTS IN CHILI SAUCE AROUND OF THE TANJUNG MORAWA TRADITIONAL MARKET WITH UV-VIS SPECTROPHOTOMETER - Sinurat, Jhon Patar; Ayuningsari, Laras; Br Karo, Reh Malem (JURNAL KESMAS DAN GIZI (JKG), 2023)
Current developments in food processing technology have made many food producers create variations in food products. Variations can include adding attractive food colorings so that consumers become enthusiastic. This good development is also disrupted because there are still some food producers who add synthetic food coloring which is not permitted to be used in food products. This happens because of a lack of knowledge and the desire of producers to make more profits, without thinking about the health impacts on the community. Synthetic dyes have a bad impact on human health, especially if they are not intended as food additives. Rhodamine-B is a synthetic dye that gives a bright red color to most cosmetic products. Rhodamine-B can irritate the gastric mucosa, eyes, skin, and respiratory tract, and trigger liver cancer. This type of research is quantitative using experimental methods in the laboratory. The samples tested were chili sauces with 5 different brands circulating in the Tanjung Morawa traditional market. Qualitative analysis using TLC was used to identify the presence of rhodamine-B in chili sauce. Comparative rhodamine-B levels and chili sauce were measured using a UV-Vis spectrophotometer at a maximum lambda of 545 nm. Chili sauces A, B, and D contain rhodamine-B dye as proven by TLC stains with Rf 0.92; 0.95; and 0.92. The linear regression equation obtained from the relationship between standard concentration and absorbance data is y = 0.0091x-0.009 with a coefficient of determination (R2) of 0.9988. Rhodamine-B levels in each chili sauce A, B, and D include 0.548; 0.505; and 0.496 mg/g. Regulation Number 722/Menkes/Per/IX/88 emphasizes that rhodamine-B is not permitted in food products because it is dangerous for body health.